Challenges faced by Malaysian private HLIs in providing quality education: a thematic analysis - Anis, Azilah; Islam, Rafikul; Abdullah, Nur Anisah (Emerald Publishing Limited, 2018)
Purpose: The paper aims to identify the emerging themes on the challenges faced by the Malaysian private higher learning institutions in the provision of providing quality education.